2001
DOI: 10.1086/323961
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Lens Statistics and the Density Profile of Dark Halos

Abstract: We investigate the inÑuence of the inner proÐle of lens objects on gravitational lens statistics, taking into account the e †ect of magniÐcation bias and both the evolution and the scatter of halo proÐles. We take the dark halos as the lens objects and consider the following three models for the density proÐle of dark halos : the SIS (singular isothermal sphere) proÐle, the NFW (Navarro-Frenk-White) proÐle, and the generalized NFW proÐle, which has a di †erent slope at smaller radii. The mass function of dark … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…For most surveys to date, such as JVAS/CLASS, the number of observed quasars is sufficiently small that each quasar can be returned to and observed in great detail. In such cases, for small‐to‐medium image separations the brightness of the lens system is seen as the total brightness of all the images, so the total magnification should be used in the bias (Takahashi & Chiba 2001; Cen et al 1994). However, for large angular separations, a lens system will only be identified if a second image is independently resolved in the survey, and therefore the magnification of the second brightest image should be used.…”
Section: Calculating the Image Separation Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most surveys to date, such as JVAS/CLASS, the number of observed quasars is sufficiently small that each quasar can be returned to and observed in great detail. In such cases, for small‐to‐medium image separations the brightness of the lens system is seen as the total brightness of all the images, so the total magnification should be used in the bias (Takahashi & Chiba 2001; Cen et al 1994). However, for large angular separations, a lens system will only be identified if a second image is independently resolved in the survey, and therefore the magnification of the second brightest image should be used.…”
Section: Calculating the Image Separation Distributionmentioning
confidence: 99%
“…Statistics of strongly lensed images promise a wealth of information about luminous and dark matter distributions and the correlations between them. For example, these statistics have yielded general constraints on the radial mass profile of early‐type galaxies (Maoz & Rix 1993; Keeton 2001b; Keeton & Madau 2001; Rusin & Ma 2001; Sarbu, Rusin & Ma 2001; Takahashi & Chiba 2001; Wyithe, Turner & Spergel 2001; Oguri 2002; Oguri et al 2002; Huterer & Ma 2004; Kuhlen, Keeton & Madau 2004). Lensing by non‐spherical mass distributions shows rich phenomenology that may be used to probe the distribution of dark matter in galaxies and clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The complementary semi‐analytic approaches often invoked simple spherically symmetric mass profiles, for calculational reasons (e.g. Hamana & Futamase 1997; Maoz et al 1997; Cooray 1999; Molikawa et al 1999; Keeton 2001; Kochanek & White 2001; Takahashi & Chiba 2001; Wyithe, Turner & Spergel 2001; Li & Ostriker 2003; Chen 2004, 2005; Huterer & Ma 2004; Kuhlen, Keeton & Madau 2004; Lopes & Miller 2004; Oguri 2006). A more advanced calculation adopted an ellipsoid for projected cluster mass distributions (Meneghetti et al 2003a; Fedeli & Bartelmann 2007; Fedeli et al 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Keeton (2001) used the statistics of JVAS/CLASS lenses to indicate that CDM galaxies are too concentrated to agree with the lensing statistics, while Keeton & Madau (2001) used the absence of wide‐separation lenses in the CLASS to impose an upper bound on the concentration of dark matter haloes. Takahashi & Chiba (2001) have considered lensing by both singular isothermal sphere (SIS) and Navarro–Frenk–White (NFW) profile galaxies, and have found that the lack of observed large‐angle separation lenses indicates that the density profile is not too steep (β≲ 1.5, with ρ( r ) ∝ r −β ). Oguri, Taruya & Suto (2001) have obtained a similar result by using the statistics of tangential and radial arcs.…”
Section: Introductionmentioning
confidence: 99%